Co-pyrolysis of hydrothermally pre-treated microalgae residue and polymeric waste (plastic/tires): Comparative and dynamic analyses of pyrolytic behaviors, kinetics, chars, oils, and in-situ gas emissions. (1st January 2023) - Kumar, Akash; Yan, Beibei; Cheng, Zhanjun; Tao, Junyu; Hassan, Mahdi; Li, Jian; Kumari, Lata; Oba, Belay Tafa; Aborisade, Moses Akintayo; Jamro, Imtiaz Ali; Chen, Guanyi
Graphical abstract: Highlights: Pyrolytic performance of microalgae residue (CSR) and polymeric waste (PS/WT) were quantified. The addition of PS/WT improved the pyrolysis performance of CSR. The average activation energy decreased (124.57 kJ/mol) with the addition of WT. Temperature-dependent behavior of evolved gaseous products were evaluated. Fuels interaction promoted hydrocarbons and impeded O- and N- containing compounds. Abstract: Biomass and polymeric wastes are becoming more problematic economically and environmentally. Their co-pyrolysis could be a cost-effective and environmentally preferable alternative for reducing waste quantities and gas emissions, as well as recovering valuable oils, chars, and gases. This study aimed to dynamically characterize the co-pyrolysis of hydrothermally treated Chlorella sorokiniana residue (CSR) and waste polymers (polystyrene (PS) and waste tires (WT)) based on their pyrolytic behaviors, kinetics, interaction effects, bio-chars, bio-oils, and in-situ evolved gasses characteristics. The devolatilization of CSR mainly occurred between 150 and 500 °C, while the decomposition of WT and PS appeared between 200–550 °C and 300–550 °C, respectively. The average activation energy was 179.25, 222.82, and 223.12 kJ/mol for the CSR, WT, and PS devolatilization, respectively. The TG-FTIR-detected functional groups included CH (stretching vibration), CH (in-plane & out-of-plane bending vibration), CC, CO2, OH, CO, COOH, CO, and NH3 . The TG-MS-detected pyrolytic products were CHO +, CH3 O +, C2 H3 O +, C3 H3 O + C3 H6 O +, C4 H3 O +, C5 H6 O +, COOH +, NH3 +, aliphatic, and aromatic hydrocarbons. Moreover, the pyrolytic oil was found to be more stable, with significantly fewer N- and O-containing compounds. It seemed that the inclusion of PS and WT in CSR pyrolysis reduce the additional fuel processing requirements to transform liquid yields into useful fuel. This research findings provide theoretical and practical insights into the control and application potential as well as the limitations of the high-value energy and products derived from the co-pyrolysis of CSR, PS, and WT.